Widening participation between 2001 and 2021 : A systematic literature review and research agenda. - Tham, Aaron; Raciti, Maria; Dale, Joshua (Journal of University Teaching & Learning Practice v.20 n.6 https://doi.org/10.53761/1.20.6.16, 2023)
Widening participation has been a vehicle to facilitate access and support towards the successful completion of university studies for underrepresented groups who are less likely to pursue higher education. Yet, despite its widely accepted importance and adoption across countries such as Australia and the United Kingdom, studies to date remain largely fragmented - often employed through the lens of a single institution, or a particular priority group. Amidst this backdrop, universities and other higher education providers are increasingly probed as to their role in supporting social capital mobility, of which widening participation plays a vital component in delivering wider societal imperatives. In addition, the COVID-19 effect has worsened university participation and completion rates, as the global pandemic has placed vulnerable students (often those involved in widening participation initiatives) in more precocious conditions than ever before. Nevertheless, the purpose of this paper is to conduct a systematic literature review comprising 102 journal articles that derive 15 meta-themes to provide a timely introspection of widening participation, show key trends over time, and chart future areas of investigation for scholars and practitioners in this space. [Author abstract]